The impact of the tumor microenvironment on macrophages - Xiao, Man; Li, Xiaoduan (Frontiers in Immunology, 2025)
The tumor microenvironment (TME), which has crucial roles in tumor progression, metastasis, and drug resistance, contains abundant immune cells. The most influential of these include tumor-associated macrophages (TAMs), which both secrete microenvironment-modifying cytokines and are acted upon by various other components of the microenvironment. The heterogeneity and diversity of TAMs are closely associated with patients’ response to tumor immunotherapy; thus, therapeutic targeting of TAMs has become a research focus in recent years. Although numerous studies have explored how TAMs alter the microenvironment, relatively few have investigated the impact of the microenvironment on TAMs. In this review, we discuss the effects of various components of the tumor microenvironment on TAMs from the perspectives of recruitment, reprogramming, and functional modulation, with a focus on the cellular components of the microenvironment. We also summarize the development of immunotherapies targeting TAMs, which have shown promising results in clinical trials.